A Commentary on Hastuti et al (2025) “Enhancing Adolescent Nutrition Knowledge Through Digital Innovation: Evaluating the Effectiveness of E-Pocket Books in Reducing Obesity” [Letter] - Khatun, Sumaiya; Hossen, Md. Sagar (Health Dynamics, 2025)
Not mandatory